The ANALISIS INDIKATOR EFISIENSI RUMAH SAKIT DI UNIT RAWAT INAP RSJ. DR. RADJIMAN WEDIODININGRAT LAWANG: Efisiensi Rumah Sakit - Ulum, Miftachul (JRMIK, 2024)
Hospital statistics are statistics that use and process data sources from health services in hospitals to produce information, facts and knowledge related to health services in hospitals. One of the hospital statistics activities is calculating hospital indicators using 4 parameters, namely BOR (Bed Occupancy Rate), AvLOS (Average Lenght Of Stay), BTO (Bed Turn Over), TOI (Turn Over Interval) which can later be used as material for decision making for hospital management. This research design uses a descriptive research with a quantitative approach, namely by providing an overview of the analysis of hospital efficiency indicators in the RSJ inpatient unit. Dr. Radjiman Wediodiningrat lawang. In this case, the object of research is the daily census sheet which will be summarized into a monthly report on hospitalization at the RSJ. Dr. Radjiman Wediodiningrat Lawang. Data collection was carried out by observation and interviews with reporting officers. This research sample uses a Saturated Sample. This research was carried out at RSJ. Dr. Radjiman Wediodiningrat Lawang. From the research results it can be concluded that the BOR indicator with a result of 82.23% is efficient. The AvLOS indicator with a result of 52.29 days is inefficient because it exceeds the specified standard, namely 3-12 days. The BTO indicator with a result of 2.89 times is inefficient because it is less than the specified standard, namely 30 times. The TOI indicator with a result of 11.30 days is not efficient because it exceeds the specified standard, namely 1-3 days Keywords: Hospital indicators and hospital efficiency.